Auden, Auden's Milton, and Songs for Virgins. (4th July 2019) - Daniel, Clay
Abstract: Deep though unexplored currents of W.H. Auden's incipient Christian theology in 'Song for St Cecilia's Day' become clearer when we read the poem with an eye on John Milton's madrigal 'At a Solemn Music' and his musical tribute to virginity, ' A Masque '. Auden closely identified Milton with the religious dualism that impeded his acceptance of Christianity, as well with the divided consciousness of the Protestantism whose disintegration was a primary source for contemporary global chaos; and his examination of art, religion, and sexuality consistently uses Milton's poems as counter-texts off which to 'bounce' his own vision of Christian flesh and Christian spirit.